On operators whose core–EP inverse is n-potent - Dijana Mosić; Daochang Zhang; Jianping Hu (Miskolc Mathematical Notes)
The main contribution of this paper is to establish a number of equivalent conditions for the core–EP inverse of an operator, to be nnnnnnnnn